The Release of 24 h Infravesical Obstruction in Mice: Changes in Molecular, Morphological, and Functional Parameters for 14-Day Observation - Lu, Yutao; Manson, Scott R.; de Araujo, Isabela Bastos Binotti Abreu; Austin, Paul F.; Djurhuus, Jens C.; Olsen, L. Henning; Nørregaard, Rikke (Frontiers in Medicine, 2022)
Bladder outlet obstruction (BOO) induces bladder dysfunction and altered bladder architecture. Irrespective of release of the obstruction, persistent bladder dysfunction severely affects the quality of life. A better understanding of the repair process offers an opportunity to enhance post-intervention management. We subsequently evaluated the post-obstructive repair process in mice subjected to 24-hour BOO followed by release. Male and female mice bladders were obstructed for 24 hours by placing a clip around the bladder neck. After the release of obstruction, the mice were studied for 3, 7 and 14 days to observe the bladder repair process over time. Voiding frequency and volume were recorded by voiding spot assay and transcutaneous glomerular filtration rate (tGFR) was measured. Fibrogenesis and associated gene expressions and altered protein levels were evaluated in the bladder using histology, QPCR and Western blot analyses. Bladder wall thickness was increased in both genders over time but occurred later in females. Moreover, collagen deposition in the smooth muscle layer increased over time in both genders. Male mice showed a decreased average voided volume at 3-day post release, while female mice showed no significant change during the time-course. Fibrosis-related molecular events, including upregulation of fibronectin (FN) protein and Col-3 mRNA expression, were transient and normalised again at 14 days in both genders. TGF-β and BMP-7 mRNA expression were upregulated at 14-day post release in both genders. Transcutaneous GFR remained normal during the time-course. Release of 24-hours bladder outlet obstruction initiated a bladder remodelling process. The animal model enables a wide range of experiments to study bladder remodelling and gender differences offer potential targets for understanding bladder fibrosis and adaptation with BOO.